Political Benefits of Community-Based Tourism Activities In Setu Babakan Betawi Cultural Village, South Jakarta - Gagih Pradini; Anisa Putri Kusumaningrum; Fitri Agustiani (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Community participation is an indicator of success in community-based tourism, a tourism destination that should include local communities in order to create collaboration and mutual benefits that synergize with each other. Betawi Setu Babakan cultural village is one of the popular destinations in Jakarta, because of its uniqueness, namely as a conservation of Betawi culture in DKI Jakarta. community participation kit in this Betawi cultural village must exist, researchers will see what the political benefits obtained by the community in pariwasata activities in the Betawi Setu Babakan Cultural Village using a qualitative research approach, in addition to using primary data, researchers also use secondary data and literature studies to take data.